A study of the foraging schedule of honeybees on soy crops as an agronomical tool to mitigate the effects of agrochemicals - Blettler, Diego César (2016)
Apis mellifera is a generalist species; however, it manifests a preference for certain flowers at fixed daytime hours and during the flowering period. Knowing this is important for crops that require pollination. In soy, even though this service is non-existent, its flowers are often frequented by the honeybee. This crop is white with frequent sanitary spraying and could give rise to the collection of contaminants by the bees along with the nectar and pollen of the flowers. Knowing the time of day when their foraging is at a maximum could be an important tool in mitigating the harmful effects of pesticides on bees and the contents of the hive. To evaluate the favourite foraging time of A. mellifera in soy, an apiary was set up close to the cultivation site and captures were carried out during the flowering period, with an entomological net at six fixed hours during day (9:00; 10:30; 12:00; 13:30; 15:00 y 16:30 h), totalling 150 raids in 3 repetitions. The results show a marked gathering preference at the time closest to noon (p=0,001) and scarce activity in the early morning and evening. A progressive increase in activity from the beginning of flowering till the maximum was reached at 12 days (p=0,019) was also seen and this implies a subsequent lessening of the same activity. These results could contribute to improving the application of phytosanitary products, particularly in proximity to apiaries, thus conserving hives and their contents.